Superior survival benefits of triple combination immunotherapy compared to standard chemotherapy as second-line treatment for advanced biliary tract cancer: a retrospective analysis - Shang, Peipei; Xu, Heming; Zeng, Tianmei; Lou, Cheng; Wei, Wei; Yang, Guang; Cheng, Zhuo; Cui, Xiaowen; Hong, Weipeng; Shen, Weidong; Lian, Zhicong; Yuan, Zhengang (Frontiers in Oncology, 2024)
BackgroundAdvanced biliary tract cancer (BTC) is associated with a poor prognosis and limited options for second-line treatment. The TOPAZ-1 and KEYNOTE-966 trials have demonstrated the benefits of combining immune checkpoint inhibitors (ICIs) with chemotherapy in treating BTC. However, the efficacy of FOLFOX as a second-line therapy is limited, highlighting the need for more effective treatment approaches.MethodsThis retrospective study compared a triple regimen—comprising ICIs, tyrosine kinase inhibitors, and chemotherapy—to standard chemotherapy in patients with metastatic BTC who had progressed on first-line gemcitabine-based therapy. The primary endpoint was progression-free survival (PFS), with secondary endpoints including overall survival (OS), overall response rate (ORR), disease control rate (DCR), and safety.ResultsOf the 121 patients, 86 received the triple regimen and 35 received standard chemotherapy. The triple regimen showed a significantly higher ORR (37.2% vs. 2.8%, p < 0.0001) and DCR (89.5% vs. 71.4%). The median PFS was 6 months for the triple regimen compared to 2.0 months for standard chemotherapy (HR 0.29, p < 0.0001). The median OS was 16.0 months for the triple regimen versus 6.0 months for standard chemotherapy (HR 0.35, p < 0.0001). Treatment-related adverse events were comparable between the groups.ConclusionThe triple combination of immunotherapy offers superior survival benefits compared to standard chemotherapy as a second-line treatment for advanced BTC, warranting further investigation for potential clinical adoption.